Golden textiles from Gokstad - Vedeler, Marianne (Archaeological Textiles Review, 2021)
Viking Age textiles with interwoven gold threads are rare in Scandinavia. Two such textiles were found in a Viking ship grave at Gokstad in Norway. Apart from brief overviews, the materials, techniques and find context of these textiles have not been described in detail before. The silk and gold embroidery was made with stem-stitch and simple laid-work. A madderdyed silk thread was used to make the flower pattern, in combination with a thread consisting of 80% pure gold lamella with a core of silk. A similar gold thread was used in a narrow band found with the embroidery. The 4 mm to 4.5 mm wide band is probably a remnant of tablet weaving. Both embroidery and band were found hidden inside a hollow ridgepole holding up the roof of a grave chamber. The precious gold and silk materials and the time-consuming and specialised technology used to make the gold thread suggests that these textiles were very valuable.